Pengaruh Lingkungan Kerja Fisik dan Kepuasan Kerja terhadap Kinerja Pegawai pada Dinas Sosial Kota Depok - Ayu Noviyanti; Pusporini Palupi Jamaludin (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The purpose of this study is to determine the effect of physical work environment and job statisfaction on employee performance at Dinas Sosial Kota Depok, both partially and simultaneously. The research method used is quantitative. The data analysis methods applied include validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient, and hypothesis testing. The sampling technique used is saturated sampling, with a total sample of 67 respondents. he results of the study show that the physical work environment (X1) and job satisfaction (X2) have a significant effect on employee performance at Dinas Sosial Kota Depok. This is proven by the regression equation Y = 26.728 + 0.647X₁ + 0.378X₂. The correlation coefficient value of 0.757 indicates a strong relationship between the independent variables and the dependent variable. The value of the determination coefficient or contribution of its influence simultaneously is 57.3%, while the remaining 42.7% is influenced by other factors outside this study. The hypothesis test results show that Fcount > Ftable (42.874 > 3.14), thus H₀ is rejected and H₃ is accepted. Therefore, it can be concluded that there is a significant influence both partially and simultaneously between the physical work environment and job satisfaction on employee performance at Dinas Sosial Kota Depok.